2011
DOI: 10.20533/iji.1742.4712.2011.0055
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Barriers in e-Government Implementation in Pakistan

Abstract: This paper presents the e-Government capabilities and thereby identifies barriers within eGovernment implementation in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…The findings also show Effort Expectancy scales that there is some hesitation for using eGovernment according to the effort. [21] argued that citizen awareness is required in implementing eGovernment practices. [13] said that the organizations which assessed did not seem to totally understand that big data applications would add price to their organizations only if they supported and were supported by all the main organizational activities.…”
Section: Proposed Frameworkmentioning
confidence: 99%
“…The findings also show Effort Expectancy scales that there is some hesitation for using eGovernment according to the effort. [21] argued that citizen awareness is required in implementing eGovernment practices. [13] said that the organizations which assessed did not seem to totally understand that big data applications would add price to their organizations only if they supported and were supported by all the main organizational activities.…”
Section: Proposed Frameworkmentioning
confidence: 99%
“…Iran: (Atashak and Mahzadeh, 2009;Yaghoubi et al, 2011;Shahghasemi et al, 2013). Pakistan: (Qaisar and Khan, 2010;Kayani et al, 2011;Haider et al, 2015).…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%
“…They found employing e-government is quite difficult especially when basic ICT infrastructure and financial resources are not available to the organization. Kayani et al (2011) examined barriers in e-government implementation in Pakistan. They found that information technology is a major barrier in the implementation of the e-government in Pakistan.…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%
“…More often, most of the active projects that were started by the previous governments are halted when a different political party comes into government, this lead to the wastage of time and resources causing huge financial losses to the country. Although GoP offers a range of services to public, but due to poor IT policies, and insufficient ICT services in the country, end user does not get benefit [17]. Since the government services lacks the transparency due to manual delivery system, therefore the citizens are either required to bribe administers to receive basic services or they are affected by the biases of officials who provide the services.…”
Section: Figure 2 Global Computer Ownershipmentioning
confidence: 99%